The Safety and Efficacy of Mesenchymal Stem Cells for Prevention or Regeneration of Intervertebral Disc Degeneration: A Systematic Review and Meta-Analyses. (May 2014) - Yim, R. Lok-hay; Lee, J.; Bow, C.; Leung, V.; Cheung, K. M. C.; Meij, B.; Vavken, P.; Samartzis, D.
Introduction: Intervertebral disc degeneration is associated with low back pain. Mesenchymal stem cells (MSCs) have been used to halt the progression or regenerate the disc with hopes to prevent or treat discogenic back pain. However, the safety and efficacy of the use of MSCs for such treatment in animal and human models at short- and long-term assessment (i.e., greater than 48 weeks) have not been systematically addressed. Therefore, the aim of this study was to perform a systematic review of comparative controlled studies addressing the use of MSCs to that of no treatment/saline for the treatment of disc degeneration. Materials and Methods: Online databases PubMed, PubMed Central, EMBASE, BIOSIS, and MEDLINE were searched. Controlled trials in animal models and humans were eligible for inclusion. Trial design, MSC characteristics, injection method, disc assessment, outcome intervals, and complication events were assessed. Validity of each study was assessed by appropriateness of randomization, blindness of outcome assessment, and sample size. Two individuals independently searched the literature, extracted data parameters, and assessed validity. Results: Twenty-four animal studies were included but no controlled studies in humans were identified. All three types of MSCs (i.e., bone marrow, synovial, and adipose tissue) showed successful tissue inhibition of disc degeneration. Bone marrow-derived MSC showed superior quality of disc repair that was marked with restoration of extracellular matrix in the disc when it was compared with other treatments, including TGF-β1, nucleus pulposus bilaminar coculture, and axial distraction regimen. However, osteophyte development was reported in two studies as a potential complication of MSC transplantation. Overall, the incidence of MSC-related complications was < 0.5%. Meta-analyses indicated that MSC increased disc space height in the majority of animal models. Conclusion: Based on the first systematic review addressing the safety and efficacy of the use of MSCs for disc degeneration prevention/regeneration, the current evidence, based on animal models, suggests that in the short-term MSC transplantation is safe and effective in halting disc degeneration; however, additional and larger studies are needed to assess the long-term regenerative effects and potential complications. Inconsistency in methodological design and outcome parameters prevent any robust conclusions. In addition, randomized controlled trials in humans are needed to assess the safety and efficacy of such therapy. Disclosure of Interest None declared